MRI-guided microwave ablation and albumin-bound paclitaxel for lung tumors: Initial experience - Shen, Xiaokang; Chen, TianMing; Liu, Nianlong; Yang, Bo; Feng, GuoDong; Yu, Pengcheng; Zhan, Chuanfei; Yin, Na; Wang, YuHuang; Huang, Bin; Chen, Shilin (Frontiers in Bioengineering and Biotechnology, 2022)
Magnetic resonance guided microwave ablation (MRI-guided MWA) is a new ablation method. This study sought to analyze the clinical value of MRI-guided MWA in Non-Small Cell Lung Cancer (NSCLC). We compared the precision, efficiency and clinical efficacy in patients that underwent MRI-guided MWA or Computed tomography (CT)-guided microwave ablation (CT-guided MWA). Propensity score matching was used on the prospective cohort (MRI-MWA group, n=45) and the retrospective observational cohort (CT-MWA group, n=305). Data including the accuracy of needle placement, scan duration, ablation time, total operation time, length of hospital stay, Progression Free Survival (PFS) and Overall Survival (OS) were collected and compared between the two groups to evaluate the advantages and efficacy of MRI-guided MWA. The mean number of machine scans required to adjust the needle position was 7.62±1.69 (range 412) for the MRI-MWA group and 9.64±2.14 (range 516) for the CT-MWA group (p＜0.001). The mean time for antenna placement was comparable for MRI and CT groups (54.41±12.32 min and 53.03±11.29 min, p=0.607). The microwave ablation time of the two groups was significantly different (7.62 ±2.65 minutes and 9.41± 2.86 minutes, p=0.017), while the overall procedure time was comparable (91.28 ±16.69 min vs. 93.41 ±16.03 min, p=0.568). The overall complication rate in the MRI-MWA group was significantly lower than the CT-MWA group (12% vs. 51%, p=0.185). The median time to progression was longer in the MRI-MWA group than in the CT-MWA group (11 months [95% CI 10.2411.75] vs. 9 months [95% CI 8.009.99], p=0.0003; hazard ratio 0.3690[95% CI 0.21590.6306]). The OS was comparable in both groups (MRI group 26.0 months [95% CI 25.02226.978] vs. CT group 23.0 months [95% CI 18.64627.354], p = 0.18). This study provides hitherto undocumented evidence of the clinical effect of MRI-guided MWA on patients with NSCLC and corroborated comparable safety and efficiency between MRI- and CT-guided MWA.